2006
DOI: 10.1148/radiol.2411050860
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodules Detected at Lung Cancer Screening: Interobserver Variability of Semiautomated Volume Measurements

Abstract: In a minority (approximately 11%) of small solid intraparenchymal nodules, semiautomated measurements are not completely reproducible and, thus, may cause errors in the assessment of nodule growth. For small or irregularly shaped nodules, an observer should check the segmentation shown by the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 20 publications
(28 reference statements)
1
74
0
2
Order By: Relevance
“…15,16 Annual CT screening studies were interpreted first at the local institution and then again at a central site. CT scans from the NELSON study have been used by investigators associated with the project to investigate, for example, interobserver variability of semiautomated lung nodule volume measurements, 17 the discrimination between benign and malignant nodules, 18,19 automated lung nodule detection, 20,21 and automated lung segmentation. 22 The research value of image databases acquired during clinical studies has been realized in other anatomic sites as well, such as CT colonography.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Annual CT screening studies were interpreted first at the local institution and then again at a central site. CT scans from the NELSON study have been used by investigators associated with the project to investigate, for example, interobserver variability of semiautomated lung nodule volume measurements, 17 the discrimination between benign and malignant nodules, 18,19 automated lung nodule detection, 20,21 and automated lung segmentation. 22 The research value of image databases acquired during clinical studies has been realized in other anatomic sites as well, such as CT colonography.…”
Section: Introductionmentioning
confidence: 99%
“…The second readers were unaware of the conclusions of the first readers. In case of discrepancy, the final decision was made by a third reader (10).…”
Section: Nelson Screen Resultsmentioning
confidence: 99%
“…Gietema et al found that interobserver correlation was very high (r = 0.99) in small-to-intermediate size (15- 500 mm 3 ) lung nodules (10). It was also found that variability on volume measurements is related to nodule size, morphology and location (16).…”
Section: Additional Results Of the Nelson Studymentioning
confidence: 99%
“…In a recent study by Gietema et al, (23) Spearman correlation coefficient analysis revealed excellent interobserver agreement between two readers for the measure of nodule volumes using a semi-automated software program in which a spherical template is used to separate nodules from surrounding structures (r = 0.99). The segmentation of small or irregularly shaped nodules was less reproducible.…”
Section: Discussionmentioning
confidence: 98%